2022
DOI: 10.1186/s12889-022-12771-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-seeking and uptake of malaria prevention strategies among pregnant women and caregivers of children under-five years during COVID-19 pandemic in rural communities in South West Uganda: a qualitative study

Abstract: Background Despite efforts to avert the negative effects of malaria, there remain barriers to the uptake of prevention measures, and these have hindered its eradication. This study explored the factors that influence uptake of malaria prevention strategies among pregnant women and children under-five years and the impact of COVID-19 in a malaria endemic rural district in Uganda. Methods This was a qualitative case study that used focus group discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Prior to the pandemic, there was a dichotomy of people avoiding and going to health centres when they were sick. Consistent with other studies, the pandemic exacerbated the dichotomy of people going to and avoiding health centres [36,38,40]. Namely, fear of exposure to COVID-19 at the hospitals and financial barriers associated with health centres (i.e., cost of care, reduced PLOS GLOBAL PUBLIC HEALTH income) led some people to avoid health centres because of the pandemic, while fear of COVID-19 and its overlapping symptoms with malaria lead some people to go to the health centre more often than before the pandemic.…”
Section: Plos Global Public Healthsupporting
confidence: 85%
“…Prior to the pandemic, there was a dichotomy of people avoiding and going to health centres when they were sick. Consistent with other studies, the pandemic exacerbated the dichotomy of people going to and avoiding health centres [36,38,40]. Namely, fear of exposure to COVID-19 at the hospitals and financial barriers associated with health centres (i.e., cost of care, reduced PLOS GLOBAL PUBLIC HEALTH income) led some people to avoid health centres because of the pandemic, while fear of COVID-19 and its overlapping symptoms with malaria lead some people to go to the health centre more often than before the pandemic.…”
Section: Plos Global Public Healthsupporting
confidence: 85%
“…Also, education on non-COVID-19 diseases was reduced [ 31 ]. A qualitative study by Taremwa et al [ 32 ] in Uganda generated similar findings, emphasising the negative effects of the pandemic on malaria by a reduced access to health care and disrupted prevention activities. The pandemic compromised health care through financial challenges, fear as well as difficulties in the clinical handling of COVID-19 alongside malaria and the associated increase in socio-economic inequities as supported by a qualitative study with focus on malaria mass testing, treatment and tracing in a rural community in the Eastern Region of Ghana.…”
Section: Discussionmentioning
confidence: 73%
“…As another consequence of the COVID-19 pandemic, the provision of rapid diagnostic tests for malaria was fragile, which may have led to under-diagnosis of cases [ 42 ]. The main explanation for the lower number of malaria cases seen in health facilities was limited access to health facilities – public transportations were unavailable or unaffordable, and health facilities were closed or only provided reduced services [ 43 , 44 ]. This is supported by findings from a study from Rwanda which showed that health facility visits for malaria decreased while community health services for malaria increased [ 43 ].…”
Section: Discussionmentioning
confidence: 99%